Strategi Penyusunan Pesan Instagram di Legitima Agensi terkait Kebutuhan Klien (studi kasus pada KNM Health Beauty) - Fitriani, Tasya Amalia; Mukaromah, (Mediakita, 2023)
Media agency is a field of work that helps manage media content on several social media. Legitim Indonesia is an agency that helps manage the preparation of Instagram messages for its clients. The purpose of this study was to find out the strategy for compiling messages carried out by Legitima Indonesia to one of its clients, namely KNM Health Beauty, which is a company engaged in the field of beauty and health. The theory used in this research is Barbara O'Keefe's message logic. The method used is a qualitative approach with case studies. The primary data are several informants from Legitima Indonesia and KNM Health Beauty. The results obtained are that the strategy for composing messages on Instagram @Knm_health_beauty is adjusted to brand segmentation that targets young, mature and economically established women. So that the message preparation strategy uses conventional logic, rhetoric and expressive message preparation patterns.